Catching the high altitude invisible by satellite-based forward scatter PCL. Issue 3 (March 2017) - Radmard, Mojtaba; Bayat, Siavash; Farina, Alfonso; Hajsadeghian, Soleiman; Nayebi, Mohammad
Abstract This paper presents a feasibility study on using satellite signal for passive radar application. Our focus is on utilizing geostationary Earth orbit satellite signal with suitable properties, like Inmarsat. Then, a new method of detection for passive coherent location using adaptive filter weights variation model is presented. To evaluate the performance, three different scenarios including a low Earth orbit satellite, a space shuttle, and a high-altitude aircraft as the targets of interest are considered. In addition to being covert, it will be shown that using such passive radar system, we can benefit the forward scatter enhancement, which enables us to detect such high-altitude targets that are normally invisible to radar systems. At last, the performance of the proposed method is compared with that of traditional methods. The analysis reveals that the proposed method has higher detection performance compared to the traditional detection methods in passive radars.